Distance Mapping of the Ankle to Assess Changes after Isolated Arthroscopic Anterolateral Subtalar Arthrodesis in Progressive Collapsing Foot Deformity - Alessio Bernasconi MD, PhD; Antonio Izzo MD; Céline Fernando PhD; François Lintz MD, PhD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Midfoot/Forefoot Introduction/Purpose: End-stage subtalar osteoarthritis in the context of Progressive Collapsing Foot Deformity (PCFD) is usually treated through subtalar joint (SJ) arthrodesis. In this study we set out to assess the changes occurring at the ankle joint after Anterolateral Arthroscopic Subtalar Arthrodesis (ALAPSTA). Methods: In this retrospective study, we evaluated pre- and post-operative (at 6 months) weight bearing computed tomography (WBCT) images of patients diagnosed with PCFD with a degenerated SJ (2A according to PCFD classification) and/or peritalar subluxation (2D) with or without associated flexible midfoot and/or forefoot deformities (1B, 1C and 1E) which underwent ALAPSTA as a standalone procedure between 2017 and 2020. Hindfoot alignment was assessed using multiple measurements. Distance Mapping (DM) at the ankle joint (divided in 9 regions) allowed to assess changes in terms of joint interaction between pre and postoperative images. Results: Out of 94 PCFD treated, thirtythree feet (33 patients, median age 62) were included in the study. Hindfoot alignment significantly improved, with a median Foot and Ankle Offset significantly decreased from 9.3 to 4 points (p< 0.001). We found a significant increase in mean distances occurring posterolaterally at the ankle (from 4.5 mm (SD 1.2) to 5.4 mm (SD 1.5), p< 0.001) along with a significant decrease occurring anteromedially (from 9.1 mm (SD 1.2) to 8.3 mm (SD 1.4), p< 0.001). In the three anterior regions there was a significant reduction of the mean distance between surfaces (all p= or < 0.01) while in two of the three posterior regions the distance between the tibia and talus significantly increased (p< 0.01). Conclusion: In patients diagnosed with PCFD undergone ALAPSTA, we observed significant changes in terms of interaction between the articular surfaces at the ankle joint, demonstrating a an external rotation and dorsiflexion on the talus in keeping with a ‘re-saddling’ effect over the calcaneus achieved through the procedure.